Faktor-Faktor yang Berhubungan dengan Kejadian Kecelakaan Kerja pada Pekerja Bagian Produkai di PT. Cahaya Agam Lestari Kabupaten Agam Tahun 2022 - Konomi, Ratna Juwita; Seno, Basuki Ario; Mukhlis, Mukhlis (Jurusan Kesehatan Lingkungan Poltekkes Kemenkes Padang, 2022)
The problem of work accidents is a major problem in the field of occupational safety and health. Based on the data obtained, starting from 2018 to 2021 there are always cases of work accidents at PT. Cahaya Agam Lestari. The purpose of this study was to determine the factors associated with the incidence of work accidents in production workers at PT. Cahaya Agam Lestari. This research is a quantitative study with a cross sectional approach which was carried out in the production department of PT. Cahaya Agam Lestari on January 10–22, 2022. The population in this study were production workers as many as 42 people, with a sample of 32 people. Data was collected through interviews using a questionnaire. Data analysis was univariate and bivariate using Chi-Square statistical test. The results showed that there was a relationship between unsafe acts and the incidence of work accidents (p = 0.004) and K3 supervision with the incidence of work accidents (p = 0.037). However, there was no relationship between unsafe conditions and the incidence of work accidents (p=0.374). To reduce the occurrence of work accidents, the company is expected to hold a safety meeting every morning, pay attention to the conditions of the work environment, such as providing adequate and proper PPE, increasing K3 supervision intensely and thoroughly and for workers to comply with applicable regulations.